PENGARUH FAKTOR INTERNAL TERHADAP PROFITABILITAS BANK UMUM SYARIAH PERIODE 2018-2022 DENGAN FAKTOR EKSTERNAL SEBAGAI VARIABEL KONTROL - Farahnizar, Aqilah Dhau'; Pimada, Laila Masruro (Contemporary Studies in Economic, Finance and Banking, 2024)
Although Islamic Banking has shown its performance as a solution-oriented bank, the Islamic banking sector still has difficulties in maintaining the stability of its profitability. In fact, to carry out its operations, banks must have high profits and when the Islamic banking sector is strong, it is very important for financial inclusion and stability of the domestic banking system. Having profitability above the minimum limit set by Bank Indonesia is the key to achieving positive banking performance. This study aims to investigate the determinants of profitability in the Islamic banking industry in Indonesia, using panel data from Sharia Commercial Banks in the period 2018 to 2022. The authors used panel data regression analysis to test the influence of CAR, NPF, FDR, and BOPO on Profitability represented by Return on Assets (ROA). Interestingly, of the four hypotheses formed, only the BOPO variable has a significant effect on profitability (ROA). This result is useful to help banking stakeholders in knowing the factors to maximize their profitability, then it is also used for government stakeholders such as the Otoritas Jasa Keuangan (OJK) and Bank Indonesia (BI) in evaluating the financial performance of Islamic banking.